Improving Speaking Skills Through the Use of YouTube "Arabic Podcast" Among Graduate Students of Higher Education - Zair Idrisa; Umi Machmudah; Penny Respati Yurisa (JURNAL IJ-ATL, 2025)
Speaking skill development in Arabic learning often faces challenges related to anxiety, limited practice opportunities, and lack of exposure to authentic spoken language. This study aims to explore graduate students’ lived experiences in using YouTube Arabic Podcasts for developing maharah kalam. Employing a qualitative phenomenological approach, the study involved graduate students as participants, with data collected through in-depth interviews and classroom observations and analyzed thematically. The findings reveal that students experience YouTube Arabic Podcasts as a flexible and learner-controlled medium that supports autonomous speaking practice. Repeated exposure to authentic pronunciation and intonation reduces speaking anxiety, enhances confidence, and gradually improves fluency. Students also demonstrate a shift in speaking orientation, prioritizing meaning-making over grammatical perfection. The novelty of this study lies in its phenomenological insight into the psychological and experiential dimensions of podcast-based Arabic speaking learning. The findings imply that integrating Arabic podcasts into speaking instruction can foster a more communicative, confidence-oriented, and learner-centered approach to maharah kalam development.